STUDY OF MIXED LAYER DEPTH VARIATION IN LIRAN ISLAND WATERS, SOUTHWEST MALUKU, APRIL 2016 - Andriana Kartina Wingtyas; Agus Anugroho Dwi; Anindya Wirasatriya; Muslim Muslim; Teguh Agustiadi (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2017)
ABSTRACTLiran Island waters are located between two seas, the Banda Sea and the Timor Sea. These waters are also the border between Republic of Indonesia and the Democratic Republic of Timor Leste (RDTL). The thickness of mixed layer depth in Liran Island waters are vary. This is assumed as a result of the influence of transition season I wind that blew in the area in April 2016. This study aims to determine the variation of the thickness layer mixed layer Liran Island waters, Southwest Maluku District on April 2016 caused by the transition season I wind.  The methodology that used in this research is descriptive method with quantitative approach. The main data that used in this study is in situ sea temperature data, while the supporting data that used in this study is wind data which measured directly in the field for 9 days. The result of this research is based on determination of layer mixed layer using criterion ΔT = 1.0 0C. The west part of Liran Island had thinnest layer mixed layer depth that is about 20 - 38 m. The east part of Liran Island waters had the thickest mixed layer depth which up to 55 m. Meanwhile, the north part of Liran Island waters had a thickness of mixed layer between the eastern and western waters of  40 m. This related to the wind that blowing from the southwest to the northeast and causing a downwelling phenomenon in the east part of Liran Island waters and upwelling phenomenon in the west part of  Liran Island waters while the north part of Liran Island waters did not get a great influence from the movement of the wind because of its location which protected by Liran Island itself. Key words: mixed layer depth, the transitional monsoon I, Liran Island waters